Mobile Live Coding Interaction and User Interface Design for Informatics Students - Patmanthara, Syaad; Nur Hidayat, Wahyu; Sutikno, Tri Atmadji; Soraya, Dila Umnia; Prasetyo, Wiji Dwi; Bramastya, Rista (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2023)
This research was conducted to design a user interface design in the form of a prototype for learning media for mobile-based basic programming courses using a User-Centered Design approach. Where this approach uses four stages in its implementation, including: 1) Analysis, 2) Design, 3) Build or Revise, and 4) User Test. The use case diagram in this user interface uses two actors, namely students and admins. The test was conducted on 10 students and vocational high school students using the short-type User Experience Questionnaire (UEQ) test method. From the tests carried out, the average results of Pragmatic Quality are 1.70, Hedonic Quality is 1.39, and Overall is 1.54. From the results of the study, it was found that the mobile learning media interface for basic programming subjects was comfortable and easy to use. Penelitian ini dilakukan untuk merancang desain user interface berupa prototype media pembelajaran mata kuliah pemrograman dasar berbasis mobile dengan menggunakan pendekatan User-Centered Design. Dimana pendekatan ini menggunakan empat tahapan dalam implementasinya, antara lain: 1) Analisis, 2) Desain, 3) Build atau Revisi, dan 4) Uji Pengguna. Diagram use case pada user interface ini menggunakan dua aktor yaitu mahasiswa dan admin. Pengujian dilakukan terhadap 10 orang siswa dan siswi SMK dengan menggunakan metode tes User Experience Questionnaire (UEQ) tipe pendek. Dari pengujian yang dilakukan diperoleh rata-rata hasil Pragmatic Quality sebesar 1,70, Hedonic Quality sebesar 1,39, dan Overall sebesar 1,54. Dari hasil penelitian diperoleh bahwa antarmuka media mobile learning mata pelajaran pemrograman dasar nyaman dan mudah digunakan.